Imported glass vessels: a review of finds in China and the Tarim Basin from the first half of the 1st millennium CE - Borell, Brigitte (Journal of global archaeology, 2025)
The paper presents an updated overview of 'western' glass vessels imported into China and into the Tarim Basin in the first half of the 1stmillennium AD. It follows a two-fold approach bringing together archaeological analysis of the visible features and published results from chemical analysis of the glasses. Three major types of glass have been discerned on the basis of their compositional analysis: Roman natron glass, and Sasanian and Central Asian plant-ash glasses. The results of this combined approach provide a more informed basis for provenancing the glass vessels and assessing a more refined date to them. It also helps to a better understanding of the glass vessels in their social contexts and the complexity of land and sea routes to be considered in the process of their transmission.